1982
DOI: 10.1212/wnl.32.5.498
|View full text |Cite
|
Sign up to set email alerts
|

Fabry disease

Abstract: Previous reports of extensive lipid accumulation within neurons of the autonomic nervous system in Fabry disease suggest an anatomicopathologic basis for the peculiar pain, diminished sweating, and gastrointestinal symptoms experienced in this disorder. To further assess autonomic function in Fabry disease, noninvasive clinical tests were performed on 10 patients. Diminished sweating was found in each; the loss was approximately uniform proximally and distally, suggesting sweat gland dysfunction rather than au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
74
0
9

Year Published

1987
1987
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(90 citation statements)
references
References 0 publications
1
74
0
9
Order By: Relevance
“…1 In affected individuals, the enzyme substrate, globotriaosylceramide (Gb3), accumulates in cells and organs, where it participates by a yet unknown mechanism in the pathologies that are characteristic of Fabry disease. 1 Disease manifestations include acroparasthesias and neuropathic pain crises [2][3][4] ; angiokeratomas; cardiac involvement, including left-ventricular hypertrophy (LVH), valvular changes, ischemia, and myocardial infarction 5 ; cerebrovascular abnormalities resulting in stroke 6,7 ; autonomic nervous system dysfunction causing decreased sweat function 8 and reduced heart-rate variability 9,10 ; and kidney dysfunction progressing to end-stage renal disease (ESRD). 11 Fabry disease occurs in people of all ethnicities with an estimated incidence of about 1 in 117,000 male births, 12 although newborn screening studies have suggested a much higher incidence.…”
mentioning
confidence: 99%
“…1 In affected individuals, the enzyme substrate, globotriaosylceramide (Gb3), accumulates in cells and organs, where it participates by a yet unknown mechanism in the pathologies that are characteristic of Fabry disease. 1 Disease manifestations include acroparasthesias and neuropathic pain crises [2][3][4] ; angiokeratomas; cardiac involvement, including left-ventricular hypertrophy (LVH), valvular changes, ischemia, and myocardial infarction 5 ; cerebrovascular abnormalities resulting in stroke 6,7 ; autonomic nervous system dysfunction causing decreased sweat function 8 and reduced heart-rate variability 9,10 ; and kidney dysfunction progressing to end-stage renal disease (ESRD). 11 Fabry disease occurs in people of all ethnicities with an estimated incidence of about 1 in 117,000 male births, 12 although newborn screening studies have suggested a much higher incidence.…”
mentioning
confidence: 99%
“…Symptoms include episodes of extremity pain or acroparesthesia, gastrointestinal symptoms, hypohidrosis and associated heat sensitivity (Cable et al, 1982;Ries et al, 2005;Rowe et al, 1974) (Table 1). Pain has been linked with small fiber neuropathy (Attal & Bouhassira, 1999) and is thought t o b e c a u s e d b y e i t h e r r e d u c e d p e r f u s i o n o f p e r i p h e r a l n e r v e s o r g l y c o s p h i n g o l i p i d accumulation in neural or perineural cells (Gadoth & Sandbank, 1983;Gemignani et al, 1984).…”
Section: Early Clinical Featuresmentioning
confidence: 99%
“…[29][30][31] Existem relatos de doentes com DF que apresentam hiperidrose, especialmente palmoplantar, que parece ser mais comum do que previamente acreditado, e mais prevalente nas mulheres. 16,[32][33][34] O pelo corporal pode ser acometido na DF na forma de hipotricose corporal difusa, pelo depósito direto de GL-3 nos folículos pilosos como também por alteração vascular de sua irrigação. 33 Outra alteração comumente detectável ao exame físico dermatológico é a presença de edema nas pálpebras e extremidades.…”
Section: Achados Dermatológicosunclassified